2019
DOI: 10.1111/cas.14084
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNAs derived from colon cancer cells promote tumor progression by suppressing fibroblast TP53 expression

Abstract: The tumor microenvironment offers favorable conditions for tumor progression, and activated fibroblasts, known as cancer‐associated fibroblasts, play a pivotal role. TP53‐deficient cancer cells are known to induce strong fibroblast activation. We aimed to elucidate the oncogenic role of exosomes derived from TP53‐deficient colon cancer cells in fibroblast proliferation and tumor growth. Cancer cell‐derived exosomes (CDEs) were isolated from the conditioned media of cancer cells using a sequential ultracentrifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 30 publications
0
70
0
Order By: Relevance
“…Exosomal miRNAs have found similar effects in colorectal cancer (CRC). Exosomal miR-2149-5p, miR-6737-5p, and miR-6819-5p can inhibit the expression of TP53 in fibroblasts to promote tumor proliferation [108].…”
Section: Reshaping Ecm To Promote Tumor Progressionmentioning
confidence: 99%
“…Exosomal miRNAs have found similar effects in colorectal cancer (CRC). Exosomal miR-2149-5p, miR-6737-5p, and miR-6819-5p can inhibit the expression of TP53 in fibroblasts to promote tumor proliferation [108].…”
Section: Reshaping Ecm To Promote Tumor Progressionmentioning
confidence: 99%
“…Exosomes are nano-sized microvesicles composed of lipid bilayer and contain various bioactive molecules, including miRNA, long non-coding RNA, circular RNAs, which are considered as mediators for intercellular communication [7,8]. Recently, exosomal microRNAs (exomiRs) have drawn much attention because numerous studies have demonstrated that exomiRs can influence many hallmarks of cancer, such as cancer development, progression, and metastasis [9][10][11][12], and more evidences have suggested that exomiRs are highly suitable candidates for use as biomarkers in an era of precision medicine [13,14]. However, the mechanisms of exomiRs in regulating the dynamic crosstalk among cancer cells and CAFs and shape the TME are still elusive.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…MiRNAs are among the most abundant cargo found in EVs; as such, it is unsurprising that EV-mediated miRNA transfer from cancer to stromal cells plays an important role in promoting CAF differentiation. To date, at least two dozen miRNAs have been found to be responsible for promoting EV-mediated CAF differentiation in a variety of cancer types [11,95,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116]. Uptake of miRNA-containing EVs into recipient cells results in altered expression of key signaling pathways, many of which have a known oncogenic or tumor-suppressive role, which leads to the adoption of a CAF phenotype.…”
Section: Mirnamentioning
confidence: 99%